2006
DOI: 10.1093/jnci/djj007
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated Soft Drink Consumption and Risk of Esophageal Adenocarcinoma

Abstract: Carbonated soft drinks (CSDs) have been associated with gastroesophageal reflux, an established risk factor for esophageal adenocarcinoma. As both CSD consumption and esophageal adenocarcinoma incidence have sharply increased in recent decades, we examined CSD as a risk factor for esophageal and gastric cancers in a U.S. multicenter, population-based case-control study. Associations between CSD intake and risk were estimated by adjusted odds ratios (ORs), comparing the highest versus lowest quartiles of intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 6 publications
4
38
1
Order By: Relevance
“…In addition, we found no significant association between high intake of carbonated soft drinks and EGJAC risk. This is consistent with the findings of other authors [6,7]. Lagergren et al [6] and Mayne et al [7] observed no significant association between high intake of carbonated soft drink and gastric cardia adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, we found no significant association between high intake of carbonated soft drinks and EGJAC risk. This is consistent with the findings of other authors [6,7]. Lagergren et al [6] and Mayne et al [7] observed no significant association between high intake of carbonated soft drink and gastric cardia adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…This null finding is consistent with the findings of the few previous reports [7,8]. In addition, we found no significant association between high intake of carbonated soft drinks and EGJAC risk.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings of no increased risk of brain cancer, although limited to malignant gliomas, are consistent with the majority of animal studies (7-9, 11) and a human case-control study on brain cancer (12): the protective association between aspartame and gliomas may be due to chance or residual confounding by other dietary/life-style factors, as suggested by another finding of an inverse association of diet soda for esophageal adenocarcinoma (24). Our findings are in direct contradiction with a recent rat study that claimed carcinogenicity of aspartame in hematopoietic, nervous, and other systems (13,14).…”
Section: Discussionsupporting
confidence: 91%